Bound manuscript documents - Dalrymple, John, Sir, 1726-1810. (1786)
Proposals on Public Questions and Colonization. "Two Measures to be proposed to Spain in which the interests of Commerce and Politics are combined, to continue during the War ..." etc.
Manuscript reference: NLA MS 1574.
Guide to collections of manuscripts relating to Australia
Author of "Memoirs of Great Britain and Ireland".
Keywords: Great Britain -- Foreign relations -- Spain -- Early works to 1800.; Spain -- Foreign relations -- Great Britain -- Early works to 1800.